Patterns of Health Care and Disability for Medicare Beneficiaries under 65 - Gerald F. Riley; James D. Lubitz; Nancy Zhang (SAGE Publishing, 2003)
Disabled people under age 65 are a vulnerable and growing segment of the Medicare population, yet Medicare reform has focused on the needs of the aged. This study linked the Medicare Current Beneficiary Survey to Social Security Administration records to analyze patterns of health care for disabled beneficiaries by reason for disability. We found substantial variation in average health care costs by type of service, including prescription drugs, and in sources of payment. Rates of institutionalization were high among some disability categories and there was heavy reliance on Medicaid and other public programs for payment. It is essential that the special needs of the disabled not be overlooked as policymakers consider fundamental modifications to Medicare and Medicaid.